Microcalorimetria de adsorção aplicada à caracterização de adsorventes para a captura de CO2. - Silva, Francisco Wilton Miranda da (2011)
Emissions of pollutant gases from the burning of fossil fuels are the main sources of gases such as CO2, which cause the greenhouse effect. In this context, the CO2 removal by adsorption has been studied as an alternative to reduce the effects to the environment. This study presents the design, assembly and experimental validation of a microcalorimetric adsorption system for simultaneous measurements of isotherms and heats of adsorption applied to the characterization of the adsorbent material. The experimental methodology was divided into three steps: the electric calibration of the microcalorimeter, the assembly of the volumetric adsorption system and the simultaneous measurements of the equilibrium and calorimetric curves of adsorption of CO2. The microcalorimeter was calibrated by the electrical input and the steady state methods. However, only the value of calibration constant, K, obtained by the electrical input was considered in the calculation of the differential heats of adsorption, because of it is more representative of the calorimetric response for the adsorption of gases. The volumetric system was constructed in stainless steel and then calibrated accurately to get the exact number of adsorbed moles at each equilibrium stage. Finally, it was obtained isotherms and differential heats of adsorption of CO2 on representative adsorbents. The samples were previously characterized for their textural properties. The activated carbon exhibited high BET surface area and micropore volume, which is characteristic of this type of material. The process of functionalization of the zeolite 13X has reduced the value of specific surface in approximately 16% due to the partial blockage of the pores by amine. In the microcalorimetric adsorption analysis, the calorimetric curves of CO2 at 273 K for the zeolite 13X agreed well with the available data in the literature, validating the microcalorimetric system. The reproducibility of the system was verified through experiments of adsorption of CO2 at 273 K on activated carbon sample. For the functionalized zeolite 13X, the differential calorimetric curve showed that the physisorption process is accompanied by the chemical adsorption phenomenon due to the presence of the amine on the surface of the solid.